Mark-to-market accounting and liquidity pricing - Franklin Allen; Elena Carletti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
When liquidity plays an important role as in times of financial crisis, asset prices in some markets may reflect the amount of liquidity available in the market rather than the future earning power of the asset. Mark-to-market accounting is not a desirable way to assess the solvency of a financial institution in such circumstances. We show that a shock in the insurance sector can cause the current value of banks' assets to be less than the current value of their liabilities so the banks are insolvent. In contrast, if historic cost accounting is used, banks are allowed to continue and can meet all their future liabilities. Mark-to-market accounting can thus lead to contagion where none would occur with historic cost accounting.
urn:nbn:de:hebis:30-30610
Keywords: G21; G22; M41; 330; Mark-to-market; Historical Cost; Incomplete Markets; Gesamtwirtschaftliche Liquidität; Bilanzielle Bewertung; Finanzmarktkrise; Versicherung; Kreditrisiko; Theorie